Effect of BiFeO3 nanoparticle on electrical, thermal and magnetic properties of polyvinyl alcohol (PVA) composite film. (August 2018) - Halder, M.; Das, A.K.; Meikap, A.K.
Graphical abstract: BiFeO3 (BFO) nanoparticles exhibit antiferromagnetic behaviour whereas BFO-PVA composite films show diamagnetism. Highlights: Conductivity increases with increasing of BFO in PVA nanocomposite. The resistivity of the films increases with lowering temperature. Characteristic relaxation time increases with BFO contents in composites. The Current-voltage characteristics of the film samples show nonlinearity. A transformation from antiferromagnetic to diamagnetic behaviour is observed. Abstract: Synthesis of BiFeO3 (BFO) nanoparticles (NPs) is demonstrated by sol-gel method. The fabrication of the flexible nanocomposite films based on different wt. % of BFO NPs and Polyvinyl alcohol (PVA) has been done by solution casting method. Conductivity as well as thermal stability tends to increase with the increase in wt. % of BFO filler in PVA matrix. Current-voltage characteristics of the composite films show nonlinearity which invokes the concept of back to back Schottky diode. Due to generation of recombination current and high leakage current, large value of ideality factor arises in the BFO-PVA nanocomposite film. Activation energies from dc conductivity and dielectric response have been evaluated and a decreasing trend in activation energy is observed with the increase in wt. % of BFO nanoparticle insertion in the PVA matrix. At room temperature, BFO NPs exhibit antiferromagnetic behaviour whereas BFO-PVA composite films show diamagnetism.